ANALISIS HUBUNGAN ANTARA MEREK SEMEN DENGAN TINGKAT KEPUASAN KONSUMEN DI KECAMATAN CITEUREUP - Ismulyana Djan; Cecep Burhanudin (Jurnal Ilmiah Binaniaga, 2006)
Indocement Tunggal Prakarsa is a cement producer that uses Tiga Roda brand name. The market share of Tiga Roda cement went down significantly from 53% 40 43% in the period of 2000 to 2004 in Bogor. The company’s global market of cement had seen some new competitors, the main competitors are Kujang, Gresik and Padang. There was an indication that Tiga Roda consumers have been brand switching to Kujang and Gresik. In order to improve Tiga Roda’s market share the writer surveyed 40 respondents at Citeureup Bogor Regency to find out the cause of this decline. In table Chi-Square Test (Table 20) showed that cement bag satisfaction has a correlation with brand name, as can be seen by the Sig. value of 0.042. This indicated that cement bag has a correlation with brand name. In table Chi-Square Test (Table 23) the price satisfaction has a correlation with brand name, as can be seen by the Sig. value of 0.001. This indicated that the price satisfaction has a correlation with brand name. In Table 5 we can see that the satisfaction average for price attribute is minor, the performance for Tiga Roda was 12.90 points. The availability of Tiga Roda product is minor, the performance was 13.5 points, and the consumers said that Tiga Roda is not easily found at the material shops. The consumers’ expectation is very important, and the most important attribute is number 13, price attribute, followed by product availability. We can see Tiga Roda consumers’ satisfaction at Cartesian Diagram (Picture 5) is as follows: 1. The main priorities are the ability to stay dehydrated and the cement color for Tiga Roda to improve performance. Respondents are not satisfied by the current ability to stay dehydrated and the cement color, respondents have an image that blackish colored cement is better. 2. The attributes that should be maintained are the easiness of cement handling and improve it if it is possible. Tiga Roda performance in this attribute is very good and is very important. 3. Low priority attribute include the shop’s service, the cement bag’s strength, bags that fulfill consumer’s needs and aesthetics values are of lower priorities. 4. Excessively valued by consumers are the product availability and price attribute, respondents appreciated the product availability and prices are very high but the company’s performances on those attributes are low.